Environmental noise exposure assessment from fireworks at festivals and pilgrimages in Northern Portugal - António Pedro Oliveira de Carvalho (2021)
Although most research related to urban noise exposure, refers mainly to transportation noise, epidemiological research has already demonstrated the risks of leisure noise exposure, including fireworks, on children, the youth, and young adults thus denoting the need for further investigation. Cumulatively, the general population living near an event's location can also feel disturbed by this type of noise. This study investigated the noise produced by fireworks at events not yet evaluated, indicating the need for better noise management by the organizers, as well as a revision of the recent European Directive in addressing exposure limits for children. The objective of this study was to evaluate the noise exposure of the population of Northern Portugal during fireworks at festivals and pilgrimages. With that purpose, measurements and questionnaires were conducted at 27 non-pyromusical and pyromusical events. Events considered to be the largest or the most traditional events which occur annually in the Northern Region of Portugal. The measurement equipment was a type 1 sound level meter, from 01 dB, positioned at the most exposed point, meaning, the area where the population was closest to the fireworks. The measurement time lasted for the entire duration of the firework explosions. The L-Aeq, L-Amin, L-Amax values, as well as the statistical indicators, L-A90, L-A50, and L-A10, were determined with an impulsive response. The results showed that in 72% of the evaluated events, the exposure level exceeded 120 dB (A, imp), the limit- value defined by the Directive 2013/29 UE. The average L-Amax, CI 95% value, for the exposed population when assisting those events, ranged between 121 and 125 120 dB (A, imp). Hypothesis tests performed for this sample, at a significance level of 5%, demonstrated that there is no significant difference between the average exposure for both types of events, non-pyromusical and pyromusical. Considering that these noise levels can induce hearing impairment this study demonstrated the need for noise control measures for the people attending these types of events. Suggested solutions highlight the following safety measures: the use of quiet fireworks, the reduction of music volume at pyromusical events, changes to the public's position and an implementation of public sessions in order to raise the population's awareness about harmful noise effects, particularly for groups that are more sensitive to noise.